Design of polyelectrolyte multilayer particles for nucleic acid delivery - Chen, Averil Min Hui (2012)
Polyelectrolyte multilayer (PEM) particles fabricated using the layer-by-layer (LbL) method provides the advantage of being highly customizable despite its simple assembly process. An array of sizes and materials can be selected for the particle template and polyelectrolyte multilayer to tailor for its anticipated purpose. Substances can be encapsulated within the core, in between the multilayer or coated on the outermost surface to provide added functionality of the resultant PEM particles. Biopolymers which are biocompatible and biodegradable are beneficial in biomedical applications of PEM particles such as carrier systems, bioreactors, biosensors, etc. The focus of this project is to bridge the gap between biomedical applications of PEM particles and delivery of active biomacromolecules through the systematic design and development of biodegradable PEM particles for nucleic acid delivery in a biological environment. Encapsulation of reporter plasmid DNA and siRNA within bio-relevant PEM particles (including PEM nanoparticles, microparticles and microcapsules) was explored as well as the interaction of these nucleic acid loaded PEM particles with HEK293T, FibroGRO and HTF cells. Furthermore, cytotoxic studies of the PEM particles were executed to determine the threshold levels for cellular applications. The long term goal is to develop the PEM particles as multifunctional tailor-made biodegradable drug carrier systems with controlled drug release and additional functionalities.